A new perspective on calmodulin-regulated calcium and ROS homeostasis upon carbon black nanoparticle exposure - Verma, Nisha; Pink, Mario; Schmitz-Spanke, Simone (Archives of Toxicology, 2021)
Toxicological studies propose that exposure to carbon black nanoparticles induces organ injuries and inflammatory responses. Besides, current understanding of the molecular mechanisms implies that carbon black nanoparticles (CBNP) exposure induces the production of reactive oxygen species (ROS) causing inflammation, mitochondrial dysfunction or disturbance in calcium homeostasis. However, the precise mechanisms whereby CBNP exert these effects in the lung are still not fully understood. To gain insight into the possible mechanism of CBNP exerted toxicity, human alveolar epithelial cells (A549) were exposed to different concentrations of CBNP and for different timepoints. The reaction of the cells was monitored by the systematic use of cell-based measurements of calcium and ROS, in the presence and absence of calcium (Ca2+) pump inhibitors/chelators and antioxidants. Followed by an in-depth PCR analysis of 84 oxidative stress-related genes. The measurements revealed, as compared to the control, that exposure to CBNP nanoparticles leads to the generation of high ROS levels, as well as a disturbance in calcium homeostasis, which remained primarily unchanged even after 24 h of exposure. Nevertheless, in presence of antioxidants N-acetylcysteine (NAC) and Trolox, ROS formation was considerably reduced without affecting the intracellular calcium concentration. On the other hand, Ca2+ pump inhibitors/chelators, BAPTA (1,2-bis(o-amino phenoxy)ethane-N, N, N′, N′-tetraacetic acid) and verapamil not only decreased the Ca2+ overload, but also further decreased the ROS formation, indicating its role in CBNP-induced oxidative stress. Further, a PCR array analysis of A549 cells in presence and absence of the calmodulin (CaM) antagonist W7, indicated toward nine altered oxidative stress-related genes which further confirmed our cytotoxicity results. Obtained data suggested that CBNP exposure elevates calcium ion concentration, which further contributes to oxidative stress, via the calcium-binding protein CaM. Its inhibition with W7 leads to downregulation in gene expression of nine oxidative stress-related genes, which otherwise, as compared to control, show increased gene expression. The results of the study thus confirm that exposure of lung epithelial cells to CBNP leads to oxidative stress; however, the oxidative stress itself is a result of a disturbance in both calcium and ROS homeostasis, and should be considered while searching for a new strategy for prevention of CBNP-induced lung toxicity.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Calcium homeostasis; Carbon black nanoparticles; Mitochondrial ROS; Reactive oxygen species (ROS)

Assessment of the different skin sensitization potentials of irritants and allergens as single substances and in combination using the KeratinoSens assay. - De Rentis, Anna; Pink, Mario; Verma, Nisha; Schmitz-Spanke, Simone (Contact Dermatitis, 2020)
People are exposed to mixtures containing allergens and irritants often causing contact dermatitis. Therefore, regulatory authorities require systematic information on the effects of mixtures on the sensitization threshold. In this study a moderate (cinnamal) and a weak (ethylene glycol dimethacrylate) allergen were combined with irritants covering different mechanisms of action (sodium dodecyl sulfate, salicylic acid, and α-pinene). For a systematic approach, the single substances were initially tested using the KeratinoSens assay. Thereafter, each allergen was combined with noncytotoxic concentrations of the irritants. The KeratinoSens assay was applied for the single substances according to OECD (Organisation for Economic Co-operation and Development) Test Guideline 442D. Based on these results, three noncytotoxic concentrations of the irritants were selected and applied simultaneously with 12 concentrations of the allergens to the KeratinoSens cells. Sensitization threshold and cytotoxicity were measured and compared with the individual testing. The combinations of allergens and irritants differed from the effects of the single substances and lowered the sensitization threshold. The quantitative approach allowed a clear description of the changes which varied by factors between 1.1 and 10.3. Overall, the allergen was the prominent compound in the mixture and its nature appeared to determine the degree of the response. BACKGROUND METHOD RESULTS CONCLUSIONS

Benchmark dose analyses of toxic endpoints in lung cells provide sensitivity and toxicity ranking across metal oxide nanoparticles and give insights into the mode of action - Pink, Mario; Verma, Nisha; Schmitz-Spanke, Simone (Toxicology Letters, 2020)
INTRODUCTION: The benchmark dose (BMD) is a dose that produces a predetermined change in the response rate of an adverse effect. This approach is increasingly utilized to analyze quantitative dose-response relationships. To proof this concept, statistical analysis was compared with the BMD approach in order to rank the sensitivity as well as the toxicity and to describe the mode of action. METHODS: Bronchial (BEAS-2B) and alveolar epithelial cells (A549) were exposed to a wide concentration range (0.4 - 100 μg/mL) of five metal oxide nanoparticles (CeO2, CuO, TiO2, ZnO, ZrO2). Eight toxicity endpoints were determined representing integrity of lysosomal and cell membrane, oxidative stress level, glutathione based detoxification (glutathione S-transferase), oxidative metabolism (cytochrome P450), alteration of the mitochondrial membrane potential, alteration of phase II antioxidative enzyme (NAD(P)H:quinone oxidoreductase), and de novo DNA synthesis. RESULTS: Based on the BMD calculated for the most sensitive test, the toxicity decreased in the following order: ZnO > CuO > TiO2>ZrO2>CeO2 in BEAS-2B. Both statistical evaluation methods revealed a higher sensitivity of BEAS-2B cells. The BMD-derived mode of action for CuO confirmed the existing hypotheses and provided insights into less known mechanisms. CONCLUSION: The findings proofed that BMD analysis is an effective tool to evaluate different aspects of risk assessment.
CRIS-Team Scopus Importer:2020-06-30
Keywords: benchmark dose; metal oxide nanoparticles; mode of action; risk assessment

Benzo[a]pyrene-induced metabolic shift from glycolysis to pentose phosphate pathway in the human bladder cancer cell line RT4 - Verma, Nisha; Pink, Mario; Boland, Stefan; Rettenmeier, Albert W.; Schmitz-Spanke, Simone (Scientific Reports, 2017)
Benzo[a]pyrene (B[a]P), a well-known polyaromatic hydrocarbon, is known for its lung carcinogenicity, however, its role in bladder cancer development is still discussed. Comparative two-dimensional blue native SDS-PAGE analysis of protein complexes isolated from subcellular fractions of 0.5 µM B[a]P-exposed cells indicated a differential regulation of proteins involved in carbohydrate, fatty acid, and nucleotide metabolism, suggesting a possible metabolic flux redistribution. It appeared that B[a]P exposure led to a repression of enzymes (fructose-bisphosphate aldolase A, glucose-6-phosphate isomerase, lactate dehydrogenase) involved in glycolysis, and an up-regulation of proteins (glucose-6-phosphate 1-dehydrogenase, 6-phosphogluconolactonase) catalyzing the pentose phosphate pathway and one carbon metabolism (10-formyltetrahydrofolate dehydrogenase, bifunctional purine biosynthesis protein). Untargeted metabolomics further supported the proteomic data, a lower concentration of glycolytic metabolite was observed as compared to glutamine, xylulose and fatty acids. The analysis of the glutathione and NADPH/NADP+ content of the cells revealed a significant increase of these cofactors. Concomitantly, we did not observe any detectable increase in the production of ROS. With the present work, we shed light on an early phase of the metabolic stress response in which the urothelial cells are capable of counteracting oxidative stress by redirecting the metabolic flux from glycolysis to pentose phosphate pathway.
EVALuna2:9763

Benzo[a]pyrene mediated time- and dose-dependent alteration in cellular metabolism of primary pig bladder cells with emphasis on proline cycling - Verma, Nisha; Pink, Mario; Kersch, Christian; Rettenmeier, Albert W.; Schmitz-Spanke, Simone (Archives of Toxicology, 2019)
Exposure to xenobiotic such as benzo[a]pyrene (B[a]P) induces metabolic changes, which have a considerable impact on the cellular response. Nevertheless, we are just in the beginning to reach an understanding of these processes. In this study, a gas chromatography–mass spectrometry (GC–MS)-based metabolomics approach was applied to distinguish the metabolic changes that bladder epithelia cells undergo upon B[a]P exposure. To closely reflect the epithelia cell conditions in vivo, freshly isolated primary porcine urinary bladder epithelial cells (PUBEC) were utilized for the current study. An untargeted metabolomics approach was used to characterize the time- (6 h, 24 h, 48 h) and dose-dependent (0.5 µM, 5 µM, 10 µM B[a]P) changes in the metabolome of PUBEC upon B[a]P exposure, which led to the profiling of more than 200 metabolites that differed significantly between control and exposed samples. Multivariate analysis of the data highlighted that in the experimental setup/model used other than the exposure concentration, it is the exposure time which seems to be most important for distinguishing between different groups and hence may have a bigger role in B[a]P-mediated toxicity but may be specific for cell model used and hence requires further investigations. Further, enrichment and pathway analysis using MetaboAnalyst highlighted that exposure to B[a]P mainly alters the cellular amino acid metabolism. Particularly, 1-pyrroline-5-carboxylic acid (P5C), an intermediate of the cycling of the amino acid proline, was identified as a differentially altered metabolite at all concentrations and exposure times used in the experiment. An increase in the activity of proline dehydrogenase/proline oxidase (PRODH/POX), which oxidizes proline to P5C, was also observed, further supporting our metabolomic data. Our findings contribute to an improved knowledge about the reprogramming of metabolism which is a fundamental element of the cellular response to B[a]P and draw attention to the role of proline in this context.
CRIS-Team Scopus Importer:2019-08-06
Keywords: Benzo[a]pyrene; Bladder cancer; Primary bladder epithelia cells; Proline metabolomics

Dose-Dependent Response to 3-Nitrobenzanthrone Exposure in Human Urothelial Cancer Cells - Pink, Mario; Verma, Nisha; Zerries, Anna; Schmitz-Spanke, Simone (Chemical Research in Toxicology, 2017)
A product of incomplete combustion of diesel fuel, 3-nitrobenzanthrone (3-NBA), has been classified as a cancer-causing substance. It first gained attention as a potential urinary bladder carcinogen due to the presence of its metabolite in urine and formation of DNA adducts. The aim of the present study was to characterize the dose-response relationship of 3-NBA in human urothelial cancer cell line (RT4) exposed to concentrations ranging from 0.0003 ?M (environmentally relevant) to 80 ?M by utilizing toxicological and metabolomic approaches. We observed that the RT4 cells were capable of bioactivation of 3-NBA within 30 min of exposure. Activity measurements of various enzymes involved in the conversion of 3-NBA in RT4 cells demonstrated NAD(P)H:quinone oxidoreductase (NQO1) as the main contributor for its bioactivation. Moreover, cytotoxicity assessment exhibited an initiation of adaptive mechanisms at low dosages, which diminished at higher doses, indicating that the capacity of these mechanisms no longer suffices, resulting in increased levels of intracellular reactive oxygen species, reduced proliferation, and hyperpolarisation of the mitochondrial membrane. To characterize the underlying mechanisms of this cellular response, the metabolism of 3-NBA and metabolomic changes in the cells were analyzed. The metabolomic analysis of the cells (0.0003, 0.01, 0.08, 10, and 80 ?M 3-NBA) showed elevated levels of various antioxidants at low concentrations of 3-NBA. However, at higher exposure concentrations, it appeared that the cells reprogrammed their metabolism to maintain the cell homeostasis via activation of pentose phosphate pathway (PPP).
EVALuna2:9762

Identification and characterization of small organic compounds within the corona formed around engineered nanoparticles - Pink, Mario; Verma, Nisha; Kersch, Christian; Schmitz-Spanke, Simone (Environmental Science: Nano, 2018)
The dynamics between biomolecules and nanoparticles, the so-called nanoparticle corona, is of great interest. It is proposed that it is the presentation of the biomolecules on the surface rather than the particles themselves which is the actual cause of numerous biological responses. While in recent years many advances have been made in analyzing the protein corona, information about other small organic components present in the corona, i.e. the organic corona, is missing although it may have a considerable influence on the biological effect of nanoparticles. The paper presented here is part of a wider research effort aimed at understanding the behavior of nanoparticles and the formation of the organic corona, in particular, of engineered nanoparticles (copper oxide, titanium dioxide, zinc oxide, zirconium dioxide, and carbon black). The particles were suspended in two different biological fluids (cell culture medium and simulated lung fluid), and the formed organic corona was then analyzed using an untargeted metabolomics approach. Several in silico analytical approaches were applied on the obtained data to assess and interpret changes in the composition of the organic corona. Principal component analysis (PCA) and enrichment analysis pointed towards amino and carboxylic groups as important determinants in the binding of the small organic compounds to the nanoparticle surface. Moreover, the biological enrichment analysis associated the identified small organic compounds with the antioxidant system and ammonia metabolism.
EVALuna2:34905

Integrated proteomic and metabolomic analysis to assess the effects of pure and benzo[a]pyrene-loaded carbon black particles on energy metabolism and motility in the human endothelial cell line EA.hy926 - Pink, Mario; Verma, Nisha; Rettenmeier, Albert W.; Schmitz-Spanke, Simone (Archives of Toxicology, 2014)
Epidemiological studies suggest that environmental exposure to airborne particulate matter may promote cardiovascular diseases; however, it is not clear whether this observation actually reflects exposure to nanosized particles in the environment. In the present study, the human endothelial cell line EA.hy926 was exposed to pure carbon black and, to mimic exposure to diesel exhaust, carbon black loaded with benzo[a]pyrene to ascertain effects of these particles on the cell proteome and metabolom. Particular emphasis was laid on an extended exposure period (14 days) and a low particle concentration (100 ng/mL). While ROS production essentially remained unaffected, exposure of the cells to the particles resulted in a significantly enhanced cell proliferation. Evaluation of the obtained proteomic and phosphoproteomic data revealed modulations of proteins involved in catalytic processes and cytoskeleton maintenance. The bioinformatic evaluation of the data revealed the possible involvement of the transcription factor peroxisome proliferator-activated receptor gamma. The further analysis of the cytoskeleton indicated changes of the cell motility, which is in agreement with an observed increase in the cellular migration and invasion, and macroscopic changes of the cytoskeleton of the exposed cells.
EVALuna2:9704

Lanthanum chloride precipitation-based toxicoproteomic analysis of 3-monochloropropane-1,2-diol toxicity in rat kidney reveals involvement of extracellular signal-regulated kinase 2 - Oberemm, Axel; Braun, Monique; Sawada, Stefanie; Pink, Mario; Frenzel, Falko; Rozycki, Christel; Meckert, Christine; Zabinsky, Elke; Braeuning, Albert; Lampen, Alfonso (Archives of Toxicology, 2017)
The heat-induced food contaminant 3-monochloropropane-1,2-diol (3-MCPD) and its fatty acid esters exert nephrotoxicity in rodents. Previous studies including a non-targeted toxicoproteomics approach using samples from a 28-day oral toxicity study in rats with 10 mg/kg body weight (b.w.) of 3-MCPD, an equimolar dose of 53 mg/kg b.w. 3-MCPD dipalmitate and a lower dose of 13.3 mg/kg b.w. of 3-MCPD dipalmitate, revealed substance-induced alterations in metabolic pathways, especially for glycolysis and energy metabolism. In order to obtain deeper insight into mechanisms of 3-MCPD toxicity, samples from the above-mentioned study were reanalyzed using a lanthanum chloride precipitation-based toxicoproteomics approach in order to increase the yield of phosphorylated proteins, crucial players in cellular signaling. A comparison of standard 2D-gel-based proteomics and lanthanum chloride precipitation was performed, thus providing a comprehensive case study on these two methods using in vivo effects of an important food toxicant in a primary target organ. While resulting in similar 2D-gel electrophoresis pherograms and spot counts, data analysis demonstrated that lanthanum precipitation yielded more significantly deregulated proteins thus considerably improving our knowledge on 3-MCPD-dependent proteomic alterations in the kidney. 3-MCPD-induced deregulation of the phosphorylated, active version of extracellular signal-regulated kinase 2 (ERK2) in rat kidney was demonstrated using mass spectrometry and immunohistochemistry. In summary, this paper for the first time links 3-MCPD effects to deregulation of the ERK/mitogen-activated protein kinase signaling pathway in rat kidney and demonstrates that lanthanum chloride precipitation is suited to support the gain of mechanistic knowledge on organ toxicity using 2D-gel-based proteomics.
EVALuna2:9761

New insights into novel inhibitors against deoxyhypusine hydroxylase from plasmodium falciparum: compounds with an iron chelating potential - Von Koschitzky, Imke; Gerhardt, Heike; Laemmerhofer, Michael; Kohout, Michal; Gehringer, Matthias; Laufer, Stefan; Pink, Mario; Schmitz-Spanke, Simone; Strube, Christina; Kaiser, Annette (Amino Acids, 2015)
Deoxyhypusine hydroxylase (DOHH) is a dinuclear iron enzyme required for hydroxylation of the aminobutyl side chain of deoxyhypusine in eukaryotic translation initiation factor 5A (eIF-5A), the second step in hypusine biosynthesis. DOHH has been recently identified in P. falciparum and P. vivax. Both enzymes have very peculiar features including E-Z type HEAT-like repeats and a diiron centre in their active site. Both proteins share only 26 % amino acid identity to the human paralogue. Hitherto, no X-ray structure exists from either enzyme. However, structural predictions based on the amino acid sequence of the active site in comparison to the human enzyme show that four conserved histidine and glutamate residues provide the coordination sites for chelating the ferrous iron ions. Recently, we showed that P. vivax DOHH is inhibited by zileuton (N-[1-(1-benzothien-2-yl)ethyl]-N-hydroxyurea), a drug that is known for inhibiting human 5-lipoygenase (5-LOX) by the complexation of ferrous iron. A novel discovery program was launched to identify inhibitors of the P. falciparum DOHH from the Malaria Box, consisting of 400 chemical compounds, which are highly active in the erythrocytic stages of Malaria infections. In a first visual selection for potential ligands of ferrous iron, three compounds from different scaffold classes namely the diazonapthyl benzimidazole MMV666023 (Malaria Box plate A, position A03), the bis-benzimidazole MMV007384 (plate A, position B08), and a 1,2,5,-oxadiazole MMV665805 (plate A, position C03) were selected and subsequently evaluated in silico for their potential to complex iron ions. As a proof of principle, a bioanalytical assay was performed and the inhibition of hypusine biosynthesis was determined by GC-MS. All tested compounds proved to be active in this assay and MMV665805 exhibited the strongest inhibitory effect. Notably, the results were in accordance with the preliminary quantum-mechanical calculations suggesting the strongest iron complexation capacity for MMV665805. This compound might be a useful tool as well as a novel lead structure for inhibitors of P. falciparum DOHH.
EVALuna2:9734

Proteomic Analysis of Human Bladder Epithelial Cells by 2D Blue Native SDS-PAGE Reveals TCDD-Induced Alterations of Calcium and Iron Homeostasis Possibly Mediated by Nitric Oxide - Verma, Nisha; Pink, Mario; Petrat, Frank; Rettenmeier, Albert W.; Schmitz-Spanke, Simone (Journal of Proteome Research, 2015)
A proteomic analysis of the interaction among multiprotein complexes involved in 2,3,7,8-dibenzo-p-dioxin (TCDD)-mediated toxicity in urinary bladder epithelial RT4 cells was performed using two-dimensional blue native SDS-PAGE (2D BN/SDS-PAGE). To enrich the protein complexes, unexposed and TCDD-exposed cells were fractionated. BN/SDS-PAGE of the resulting fractions led to an effective separation of proteins and protein complexes of various origins, including cell membrane, mitochondria, and other intracellular compartments. Major differences between the proteome of control and exposed cells involved the alteration of many calcium-regulated proteins (calmodulin, protein S100-A2, annexin A5, annexin A10, gelsolin isoform b) and iron-regulated proteins (ferritin, heme-binding protein 2, transferrin). On the basis of these findings, the intracellular calcium concentration was determined, revealing a significant increase after 24 h of exposure to TCDD. Moreover, the concentration of the labile iron pool (LIP) was also significantly elevated in TCDD-exposed cells. This increase was strongly inhibited by the calmodulin (CaM) antagonist W-7, which pointed toward a possible interaction between iron and calcium signaling. Because nitric oxide (NO) production was significantly enhanced in TCDD-exposed cells and was also inhibited by W-7, we hypothesize that alterations in calcium and iron homeostasis upon exposure to TCDD may be linked through NO generated by CaM-activated nitric oxide synthase. In our model, we propose that NO produced upon TCDD exposure interacts with the iron centers of iron-regulatory proteins (IRPs) that modulate the alteration of ferritin and transferrin, resulting in an augmented cellular LIP and, hence, increased toxicity.
EVALuna2:9715

ROS and pentose phosphate pathway: mathematical modelling of the metabolic regulation in response to xenobiotic-induced oxidative stress and the proposed Impact of the gluconate shunt - Schittenhelm, Doris; Neuss-Radu, Maria; Verma, Nisha; Pink, Mario; Schmitz-Spanke, Simone (Free Radical Research, 2019)
Elevated intracellular levels of reactive oxygen species (ROS), e.g. resulting from exposure to xenobiotics, can cause severe damages. Antioxidant defence mechanisms, which involve regulation of enzyme activities, protect cells to a certain extent. Nevertheless, continuous or increased exposure can overwhelm this system resulting in an adverse cellular state. To simulate exposure scenarios and to investigate the transition to an adverse cellular state, a mathematical model for the dynamics of ROS in response to xenobiotic-induced oxidative stress has been developed. It is based on exposure experiments of human urothelial cells (RT4) to the nitrated polycyclic aromatic hydrocarbon 3-nitrobenzanthrone (3-NBA), a component of diesel engine exhaust, and takes into account the following metabolic pathways of the antioxidant defence system: glutathione redox cycle scavenging directly ROS, the pentose phosphate pathway and the gluconate shunt as NADPH supplier and the beginning of glycolysis. In addition, ROS generation due to the bioactivation of 3-NBA has been implemented. The regulation of enzyme activities plays an important role in the presented mathematical model. The in silico model consists of ordinary differential equations on the basis of enzyme kinetics and mass action for the metabolism of 3-NBA. Parameters are either estimated from performed in vitro experiments via least-squares fitting or obtained from the literature. The results underline the importance of the pentose phosphate pathway to cope with oxidative stress and suggest an important role of the gluconate shunt during low-dose exposur
Keywords: mathematical modelling; ROS metabolism; oxidative stress; 3-nitrobenzanthrone (3-NBA); gluconate pathway

Toxicological endpoints and metabolomics analysis reveal a transition from adaptive to adverse cellular state of 3-nitrobenzanthrone in urothelial cells - Schmitz-Spanke, Simone; Pink, Mario; Zerries, Anna; Verma, Nisha (2017)

Weltkongress zum Biomonitoring mit starker deutscher Beteiligung - Drexler, Hans; Göen, Thomas; Schmitz-Spanke, Simone; Klotz, Katrin; Pink, Mario (Arbeitsmedizin, Sozialmedizin, Umweltmedizin, 2017)
CRIS-Team Scopus Importer:2020-05-11